PELAKSANAAN AKUNTANSI PERTANGGUNG-JAWABAN BIAYA TENAGA KERJA PADA PERUSAHAAN RITEL (Studi pada PT. Rita Ritelindo Purwokerto) - Wibowo, Raden Arief (PERMANA, 2015)
This research entitled âThe Evaluation for Implementation of Employerâs Cost Responsibility Accounting in Rita Ritelindo Purwokertoâ. The aims to know whether appropriate or not the implementation of employerâs cost responsibility accounting in Rita Ritelindo Purwokerto.Â The hypotheses is the implementation of employerâs cost responsibility accounting in Rita Ritelindo Purwokerto havenât appropriate yet. Descriptive t test is the analysis tool.Â The conclusiont, the implementation of employerâs cost responsibility accounting in Rita ritelindo Purwokerto is already appropriate.Â The implications of this research is, to keep the accounting system of Rita Ritelindo Purwokerto need to pay attention on organizational structure such as job description and job dividing for each personal. There should be clear and detail organizational structure.Â Keywords: Ritel, responsibility accounting, cost accounting